Profitability analysis of giant african land snail marketing in Delta North, Nigeria - Okonta, B. O.; Gbigbi, T. M.; Imitini, E. S. (International Journal of Agricultural Technology, 2021)
Result found that the majority of the snail marketers were female and married with mean age of 40 years. The mean household size was 5 persons. Majority of the snail marketers are educated with mean marketing experience of 9years. The majority of snail marketers (76.92%) did not belong to an Association, and the mean income was N90,640. The total revenue was N171,129.24k and total cost was NI 15,262.16k. The marketing margin was N55,867.08k and also the benefit cost ratio and return on investment was 1.48 and 0.48, respectively. The marketing efficiency of snail marketers was 114.84%. The variables transportation cost, selling price, market levies, quantity of snail sold, loading and offloading cost influence profitability of its marketing. The major constraints affecting snail marketing were insufficient showed in credit facilities, transportation cost, price fluctuation, inadequate market information and inadequate storage facilities. The most predominant snail marketing channel was producer-wholesalers-retailers-consumers. The study concluded that giant African Land snail marketing was a profitable venture in the study area. The formation of cooperative societies is recommended and should be encouraged to enhance marketing especially in the area of purchasing large quantity